Administrative and Judicial Discretion in Procedural Decision Making under the Code of Administrative Offenses of the Russian Federation - S. V. Schepalov (Сибирское юридическое обозрение, 2025)
This article continues the scholarly discussion initiated by Professors Yu. P. Solovey, P. P. Serkov, and S. A. Starostin on the issue of administrative discretion. Drawing on the theoretical framework proposed by Yu. P. Solovey, the Author compares administrative and judicial discretion in the context of Russian administrative jurisdiction, analyzing their respective functions, goals, subjects, and legal nature. As a result, the article proposes scientifically grounded definitions of both legal phenomena. The law does not, as a rule, provide enforcement authorities with a fully developed set of options for resolving a case. Consequently, a jurisdic-tional authority often cannot exercise discretion simply by choosing the “correct” option from a predefined list. Instead, the decision-making process is frequently complex, requiring not only analytical but also synthetic and creative approaches. In this context, the Author suggests using the broader term “decision-making” rather than simply “choice,” even while acknowledging the validity of defining discretion as a form of selection. Administrative discretion is understood as an instrument for achieving the goals of state policy and the execution of public authority. It focuses on implementing law in its narrow normative sense and involves compensating for legislative gaps by interpreting and applying the “spirit” of the law. By contrast, judicial discretion is oriented toward realizing universally recognized norms and societal values that express the broader priorities of the state. It represents law in its integrative sense – as a synthesis of fundamental social values and norms that reflect a societal consensus. Accordingly, the Author defines administrative discretion in administrative jurisdiction as the act of decision-making by an official in a case concerning an administrative offense, guided by their understanding of legal norms and values that correspond to the strategic priorities of public governance. Judicial discretion is defined as the act of a judge making a procedural decision based on their own understanding of widely accepted social norms within which the law is to be applied.